Three new species of spiny mice, genus Neacomys Thomas, 1900 (Rodentia: Cricetidae), from Brazilian Amazonia. Issue 8 (17th November 2021) - Semedo, Thiago Borges Fernandes; Da Silva, Maria Nazareth Ferreira; Carmignotto, Ana Paula; Rossi, Rogério Vieira
Abstract : Spiny mice of the genus Neacomys Thomas, 1900 are small oryzomyines that occur in forested habitats from Panama to central Bolivia. Previously known by only four species, systematic revisions provided great increase in genus species richness, which currently comprises 20 valid species. Herein we raise this number to 23, describing three new species of spiny mice. The new taxa are found in western and central Brazilian Amazonia in the states of Amazonas and Pará, and their geographic distribution are delimited by major rivers, being coincident with previously described Amazonian centers of endemism: (1) Neacomys aletheia, sp. nov., ranging from the right and left bank of the Rio Juruá, Amazonas state, Brazil to Loreto in Peru, from the Inambari center; (2) Neacomys jau, sp. nov., distributed between the Rio Negro and Rio Solimões, Amazonas state, Brazil, from the Imeri center; and (3) Neacomys elieceri, sp. nov., restricted to the Rondônia endemism center, between the Rio Tapajós and Rio Madeira, Pará state, Brazil. Previously reported more than 20 years ago as putative new species based on molecular and cytogenetic data, morphological analyses now reinforce the validity of these forms. Based on the analysis of 78 specimens, including name-bearing types from most of the distributional range of Neacomys, we formally describe and name these undescribed species. The new taxa can be distinguished from other closely related Neacomys by a set of qualitative traits, such as dorsal and ventral pelage coloration, tail color, morphology of the nasal bones, interorbital region, paraoccipital process, sphenopalatine foramen, incisive foramina, zygomatic plate, auditory bullae, foramen accessorius, anterocone and anteroloph of first upper molars, in association with cytochrome b gene sequences, and karyotype. These data increase the currently known Neacomys diversity, and also contribute to elevate Amazonian sigmodontinae species richness and endemism, in this yet poorly surveyed biome. urn:lsid:zoobank.org:pub:1721BB20-3542-4959-B95E-A36B0D522F39